Open Skies Policy: The Developing Countries Point of View - Wiradipradja, E. Saefullah (UI Scholars Hub, 2021)
The concept of open skies policy is an international policy concept which aims to liberalize of rules and regulations on international commercial aviation industry. For developed countries, by allowing air carriers unlimited market access to its partners’ markets and the right to fly to all intermediate and beyond points, open skies agreements provide maximum operational flexibility for airline alliances. They may have the best opportunities, as they will be able and in the best position to offer the best product to the better part of the air traffic market. On the contrary, for developing countries, open skies policy may cause more harm to the interests of airlines than bring economic gains to the countries. Further, it will lead to a domination of the international air transportation market by the biggest and most developed countries that finally it will return the situation to monopolistic system. To take care of emerging needs, it would be more appropriate to periodically renegotiate the existing bilateral agreements.